Pemamfaatan Media Canva pada Pembelajaran Pembuatan Poster Siswa Kelas X MA Pondok Pesantren Darul Akhlaq Toronan Pamekasan - Cony Elok Safitri Romdani; Sri Wahyuni (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The demands of the era of rapid digitalization require every group to be able to adapt and continue to increase their competitiveness with digital technology. Especially in the world of education, in the era of digitalization, everything can be accessed easily, the digital world provides a change in the era of learning that can be carried out with a wider reach. Students can easily access assignments and learning by accessing them on the internet. However, the case is different if within the scope of an Islamic boarding school, which in fact does not allow its students to bring cell phones/gang phones. The main aim of this research is to examine cases that occur in the field regarding these problems, and also to participate in case studies that occur in the Islamic boarding school environment. The research design uses a descriptive case study research approach where researchers will go directly to the field to observe and research how cases occur in the field. The main instruments in this research are teachers and students. The main finding obtained by researchers is how the use of Canva media in learning to make posters is still not optimal and experiences several obstacles. The results of the research show that in using Canva media in learning to create, students have experienced an increase not only in making posters in writing but also in how the design and quality of the posters produced has increased by 80%.